SIMULASI HIDROTERMAL DAERAH KAWAH DOMAS DENGAN PEMODELAN KONTINU 2-D ANOMALI SELF POTENTIAL (SP) - Rena Denya Agustina (Journal of Teaching and Learning Physics, 2017)
Hydrothermal system research using Self Potential (SP) Method, 2-D DC Resistivity and surface temperature, has been done at Domas Crater (1700 masl). Potential anomaly which is associated with subsurface structure is obtained by SP measurement, whereas temperature measurement is done to get information about surface temperature distribution laterally and resistivity distribution of volcano structures is known by 2-D DC Resistivity measurement. Hydrothermal activities, which cause the existence of SP value, are modeled using this scheme modeling. This schema modeling is validated by comparing the value of SP model with field measurement. The shallow hydrothermal activities at Domas Crater are influenced by meteoric and subsurface water. The velocity of hydrothermal activities are about 10-9 - 10-7 m/s. 16.64% root mean square error is obtained by Comsol modeling, whereas 6.54% root mean square error is obtained by modeling using finite element method.